Trends and factors associated with intimate partner violence against women in Peru: Results of three Demographic and Family Health Surveys - Roque Henriquez, Joel Christian (2024)
Objetive: To determine the trend in the prevalence of the different types of intimate partner violence against Peruvian women, and the factors associated with such outcomes. Materials and methods: Research based on three Demographic and Family Health Surveys conducted in Peru. The study population was women from 15 to 49 years old, selected and interviewed for the domestic violence module and with marital status married or living together. Results: There was a decreasing trend of the different types of intimate partner violence against women (p value < 0.001); as well as, control situations, humiliating situation and threat situations (p value < 0.001). The husband's or partner's alcohol consumption, the history that the woman's father ever hit her mother, a greater number of children alive, control situations, humiliating situation, and threatening situations showed an independent effect for intimate partner violence (aRP > 1, p value < 0.05). No association was found with the wealth index, educational level of the woman and her partner (p value ≥ 0.05). Conclusions: There is a decreasing trend in the prevalence of the different types of intimate partner violence against women. The husband's or partner's alcohol consumption, the history that the woman's father ever hit her mother, a greater number of children alive, control situations, humiliating situation, and threatening situations showed an independent effect for intimate partner violence.